Perlindungan Hukum terhadap Konsumen Produk Rekayasa Genetik di Indonesia - Anto Ismu Budianto (Jurnal Hukum IUS QUIA IUSTUM, 2000)
Genetic engineering as the application of biotechnology can be considered as an advance inthe fields of technology and science to satisfy human's needs in farming, health,and industry. Apart from pro and contra matters about genetic engineering products concerning whether or not these products are safe for human beings, the most important thing to consider is the legal protection towards people who consume them. The regulation in the forms of Acts concerning the safety of the engineering products seems to be necessary recently, due to the emerging possibilities in the field of human health and environmental care.